Salvage Pulmonary Operations Following Stereotactic Body Radiotherapy for Small Primary and Metastatic Lung Tumors: Evaluation of the Operative Procedures. (12th November 2018) - Hamakawa, Hiroshi; Takahashi, Yutaka; Sakanoue, Ichiro; Saito, Tomoki; Date, Naoki; Tomii, Keisuke; Katakami, Nobuyuki; Imagunbai, Toshiyuki; Kokubo, Masaki
Stereotactic body radiotherapy is an alternative treatment option for small-sized, primary lung cancers and pulmonary metastatic diseases. In the case of local relapse after stereotactic body radiotherapy, salvage pulmonary resection is considered cautiously. However, no study has described the difficulty of the salvage operations. This study aimed to assess the difficulty associated with salvage operative procedures. Eight patients who developed local relapse after stereotactic body radiotherapy and had undergone salvage pulmonary operations were enrolled in this study (stereotactic body radiotherapy group). Additionally, 439 patients who underwent video-assisted thoracoscopic lobectomy without previous stereotactic body radiotherapy were enrolled as the standard operative control group (non-stereotactic body radiotherapy group). In the stereotactic body radiotherapy group, 1 of the 8 patients had undergone lobectomy with composite resection of the third and fourth ribs. Of the 8 patients, 6 had undergone video-assisted thoracoscopic lobectomy and 1 had been inoperable because of rapid tumor progression. The operation time and the incision length of the utility port were apt to be longer in the stereotactic body radiotherapy group than in the non-stereotactic body radiotherapy group. On the contrary, the duration of drain placement and the length of hospital stay after the operation were not different. Thus, the salvage pulmonary operations were performed in the usual video-assisted thoracoscopic lobectomy approach, but slightly complicated than the standard video-assisted thoracoscopic lobectomy. Although to decide the indication of salvage operation might be difficult, it could be a feasible treatment option in local relapse after stereotactic body radiotherapy.